(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: This paper discusses the effect of terrorism and wars on the hotel industry of hotel management students. Methods: The impacts of these negative situations were tested from the data collected from 265 students of various courses at the institute using a questionnaire. Results: It was found that majority (49.8%) of the students do not regret in joining the industry after terror attacks like that of 26/11. Also majority (62.9%) agrees to recommend hotel management profession to their friends and they are not regretful of joining the profession.